2015
DOI: 10.1111/resp.12477
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of combined therapy with pirfenidone and inhaled N‐acetylcysteine for advanced idiopathic pulmonary fibrosis: A case–control study

Abstract: Combination treatment with inhaled NAC and oral pirfenidone reduced the rate of annual FVC decline and improved PFS in patients with advanced IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 27 publications
1
69
1
Order By: Relevance
“…Replication of our findings in this manner would identify an inexpensive, readily available therapy for approximately 25% of individuals with IPF and determine whether NAC is detrimental to those carrying both rs3750920 ancestral alleles. Such a trial would also be an excellent opportunity to explore synergy between NAC and newly approved therapies for IPF, as has been recently suggested (19). Finally, our findings highlight the importance of pharmacogenetics in IPF and strongly support an effort to systematically acquire biospecimens from all individuals participating in clinical trials.…”
Section: Original Articlesupporting
confidence: 73%
See 1 more Smart Citation
“…Replication of our findings in this manner would identify an inexpensive, readily available therapy for approximately 25% of individuals with IPF and determine whether NAC is detrimental to those carrying both rs3750920 ancestral alleles. Such a trial would also be an excellent opportunity to explore synergy between NAC and newly approved therapies for IPF, as has been recently suggested (19). Finally, our findings highlight the importance of pharmacogenetics in IPF and strongly support an effort to systematically acquire biospecimens from all individuals participating in clinical trials.…”
Section: Original Articlesupporting
confidence: 73%
“…Oxidative signaling plays a key role in the lung immune response, and can be modulated by the presence of antioxidants, such as N-acetylcysteine (NAC) (15)(16)(17). Although NAC therapy was recently shown to be no better than placebo in treating IPF (18), it remains a common off-label therapy for the disease (19,20). Whether polymorphisms in TOLLIP and MUC5B influence antioxidant effects is unknown.…”
mentioning
confidence: 99%
“…Other investigators are looking to see if additional benefit may be seen from combination therapy with pirfenidone and inhaled NAC when compared to pirfenidone alone [38]. The sense of hopefulness is not shared by all clinicians it seems, as many experts question the role of pirfenidone or nintedanib in all patients, or restricting use to patients who met the criteria of the clinical trials that evaluated their use [39], a practice that would remove many patients with severe IPF from qualifying for treatment.…”
Section: Adverse Effectsmentioning
confidence: 97%
“…Pirfenidone decreases PSCs proliferation, invasion and migration in vitro and inhibits subcutaneous tumor formation in mice co-transplanted with PCCs and PSCs [11]. A recent study has shown a better patient outcome with combined therapy of pirfenidone and N-acetylcystein (NAC) in advanced idiopathic pulmonary fibrosis patients [12]. Moreover, NAC sensitizes human PCCs to gemcitabine by inhibiting NFκB pathway [13]; and cultivation of PSCs on extracellular matrix proteins and treatment with NAC induced deactivation of PSCs and reduced their proliferation and fibrogenic property [14].…”
Section: Introductionmentioning
confidence: 99%